Evaluation of spinal fractures and dislocations in 80 cats and 32 dogs: A clinical retrospective study - Altuğ, Muhammed Enes; Kırgız, Ömer; Yurtal, Ziya; Yılmaz-Deveci, Mehmet Zeki; Alakuş, İbrahim and Alakuş, Halil and Ceylan, Eren and Öründü, Nimet and Kaya, Ufuk and İşler, Cafer Tayer (Revista Científica de la Facultad de Ciencias Veterinarias, 2025)
In this study, besides the etiological causes of spinal fractures and dislocations of cats and dogs, the effects of the posttraumatic period, deep pain sensations and trauma localization on recovery were evaluated. A total of 112 animals, including 80 cats (71.43%) from 8 different breeds and 32 dogs (28.57%) from 9 different breeds, with spinal fractures and/or dislocations were included in the study. In the neurological evaluation, paraplegia, tetraplegia, paraparesis, tetraparesis conditions were recorded. Considering the neurological and radiographic examination results, the trauma area was classified as cervical (C1–C5), cervico-thoracic (C6-Th2), thoracolumbar (Th3–L3) and lumbosacral (L4-S3), according to the affected spinal cord segment. In the current study, it was observed that falling from a height was more common in cats exposed to spinal traumas, and vehicle accidents were more common in dogs. It was determined that cats and dogs exposed to spinal trauma were mostly domestic and adult. In cats, spine fractures were seen the most (58/80, 72.5%), followed by spine dislocations (20/80, 25%), and fractures and dislocations in combination (2/80, 2.5%). In dogs, it was similar to that of cats (24/32, 75%; 7/32, 21.88%; and 1/32, 3.13%, respectively). The most affected vertebrae range was found to be between Th3-L3 in cats (40/80, 50%) and L4-S3 in dogs (18/32, 56%). The recovery rate was higher in cats and dogs where the spine segment between L4-S3 was affected. The recovery status of the cases brought within the first 24 hours was better. When neurological conditions were examined, it was determined that, compared to cases without deep pain sensation, recovery rates were higher in cases with paraparesis and deep pain sensation. In the light of all these data, it was concluded that euthanasia would not be a priority choice in the first place, as there were also patients who recovered, albeit at a very low rate, among the cases without deep pain sensation.